Multistage Regulation Strategy via Fluorine‐Rich Small Molecules for Realizing High‐Performance Perovskite Solar Cells - Xiong Chang; Kunpeng Li; Yong Han; Guohua Wang; Zhishan Li; Dongfang Li; Fashe Li; Xing Zhu; Hua Wang; Jiangzhao Chen; Tao Zhu (Advanced Science)
Abstract Perovskite solar cells (PSCs) are an ideal candidate for next‐generation photovoltaic applications but face many challenges for their wider application, including uncontrolled fast crystallization, trap‐assisted nonradiative recombination, and inefficient charge transport. Herein, a multistage regulation (MSR) strategy for addressing these challenges is proposed via the introduction of fluorine‐rich small molecules with multiple active points (i.e., 1‐[Bis(trifluoromethanesulfonyl)methyl]‐ 2,3,4,5,6‐pentafluorobenzene (TFSP)) into the precursor solution of the perovskite film. The addition of TFSP effectively delays and regulates the crystallization and growth process of the perovskite film for larger grains and fewer defects, and it effectively improves the coverage of self‐assembled molecules for efficient charge transport. The multiple active points of TFSP induce a strong binding affinity with uncoordinated defects in the perovskite film. Moreover, the high fluorine content of TFSP induces strong electronegativity to establish a high binding strength between the perovskite film and electron transport layer. Finally, PSCs prepared by the MSR strategy demonstrated an optimal power conversion efficiency (PCE) of 25.46% and maintained 91.16% of the initial PCE under nonpackaged air conditions and at a relative humidity of 45% after 3000 h.